Identifying corners of clothes using image processing method - Hou Y.C.; Sahari K.S.M. (2023)
This paper presents a method to identify the edges and corners of clothes in an image using image processing methods. In clothes manipulation, it is important for the GUI program to identify the shape of clothes before spreading and folding. The first step for clothes manipulation is that the robot needs to grab two real corners so the clothes can be spread easily. The computer vision system becomes an important part in finding the corner of clothes. With the help of image processing, the corner of clothes can be identified for the robot to spread and fold the clothes. This method to identify the corner of clothes in the image is by applying certain image processing methods. Some basic morphological operations are used to filter the image captured in order to reduce the noise and disturbance and also extract the essential data from the image for further processing. The purpose of using this method is to identify the pixel in the image which is potentially represented as a corner of the clothes and become a starting point for the robot in clothes manipulation.